UNLOCKING HIDDEN DEMAND: UTILIZING COMPUTER VISION FOR STREET HAILING OPTIMIZATION IN BLUE BIRD TAXI - Ferrizal
Despite the technology disruption from online ride-hailing, street-hailing is still popular in among certain people in Jakarta, the capital city of Indonesia. The taxi firms still count street hailing as a highly reliable service that offers unique benefits to both passengers and drivers as opposed to the online services. The easy experience and swift decision of hailing a taxi have a sense of immediacy that cannot be replicated by online apps. However, the classic street hailing service faces a few challenges, especially for Blue Bird as one of the taxi operators in Jakarta. Unlike ride hailing apps where demand is recorded digitally, street hailing is often lack of visibility into street demand, leading to fleet operation inefficiency. This is where Computer Vision (CV) technology offers an innovative approach to improve visibility and identify the unmet demand for street-hailing, by capturing the gestures of people hailing a taxi from the street and count it as a demand for future analysis.